2006
DOI: 10.1177/197140090601900511
|View full text |Cite
|
Sign up to set email alerts
|

Falx Cerebri Ossification: CT and MRI Evaluation

Abstract: During the last three years, CT and MRI brain scans of 40 patients revealed falx cerebri partial ossification as an incidental finding. The patients had been admitted for brain CT and MRI for several reasons. In most cases, there was no problem in the differential diagnosis of falx cerebri ossification during interpretation of the cases. In a few cases, the lesion should be distinguished from calcified meningioma, small hematoma in the interhemispheric fissure and in one case there was also meningeal infiltrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…[8,21,24,26,28,30] The predominance of anterior (and medial) distribution of FCC corresponds to the opinion of most authors. [11,13,17,19,24,29,31] Using 178 FCC on medio-sagittal images of x-ray tomography Lanig [24] calculated a 99% probability that the anterior accumulation of FCC in his sample is not random. In contrast to observations made by Tsitouridis [13] considerably more cases of multiple FCC occurrences in one patient were discovered (about half of all patients examined).…”
Section: Data-discussion-and Comparison With Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…[8,21,24,26,28,30] The predominance of anterior (and medial) distribution of FCC corresponds to the opinion of most authors. [11,13,17,19,24,29,31] Using 178 FCC on medio-sagittal images of x-ray tomography Lanig [24] calculated a 99% probability that the anterior accumulation of FCC in his sample is not random. In contrast to observations made by Tsitouridis [13] considerably more cases of multiple FCC occurrences in one patient were discovered (about half of all patients examined).…”
Section: Data-discussion-and Comparison With Previous Studiesmentioning
confidence: 99%
“…[8] Few studies which also included histological examinations usually described FCC (except for occasional psammoma bodies) as a typical ossification. [10][11][12][13][14][15] Concerning the identification of intracranial calcifications, the CT is significantly superior to other imaging methods. [16][17][18][19] Only three CT studies could be found examining FCC frequency.…”
Section: Introductionmentioning
confidence: 99%
“…They may also involve the choroid plexus of the lateral ventricles. Most often, such ossifications or calcification are clinically irrelevant and cause no neurological symptoms: neither focal deficit symptoms nor irritating symptoms -epileptic seizures [1][2][3]. They also do not cause increased intracranial pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Most often they are accidentally diagnosed during head imaging examinations performed for various medical indications. The imaging test of choice, which most clearly shows ossification is computed tomography (CT) [3]. In CT, calcifications are clearly distinguishable from brain tissue and cerebrospinal fluid because they are definitely hyperdense.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation